EFFECT OF KANGAROO MOTHER CARE (KMC) ON THE FORMATION OF MATERNAL-INFANT ATTACHMENT BETWEEN MOTHERS AND PREMATURE BABIES: A LITERATURE REVIEW - Zubaidah, Zubaidah; Safitri, Ayu Diah (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Nursing care of premature babies in the Neonatal Intensive Care Unit (NICU) setting can inhibit the maternal-infant attachment. One of the evidence-based interventions for premature babies is Kangaroo Mother Care (KMC). KMC needs to be further studied and researched through a review of previous articles to ensure the effectiveness of that implementation. However, there is a very limited review that specifies the effect of KMC on the formation of maternal-infant attachment. Objective: This study was conducted to assess the effect of KMC on maternal-infant attachment between mothers and premature babies. Design: The design of this study uses a literature review. Data Sources: Initial searches of journal articles were performed on the Pubmed, ScienceDirect, and CINAHL search databases. The study found 676 articles but only 7 journal articles that met the search inclusion criteria. Review Methods: A literature review procedures were used to collect library data, reading and taking notes, as well as critical assessment of managing research materials. Results: The results of this review showed that KMC has been shown to have a positive impact on improving attachment status and resulting in a lower risk of bonding failure between mothers and premature babies. Conclusion: It is recommended that health workers can provide treatment using KMC as an intervention to improve the formation of maternal-infant attachment between mothers and premature babies. The policies related to the implementation of KMC as standard operating procedures are also important.